Analisis Disiplin Kerja Pada PT. Mekada Abadi Medan - Ricko Rayliem; Yuliana; Arwin (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this study was to determine the discipline of employees at PT. Mekada Abadi Medan. In this study, the method used is a descriptive qualitative method. The data collection technique used is structured interview. The sampling technique used is purposive sampling. Data obtained from structured interviews were carried out through validity checking using source triangulation. In sampling, the number of informants interviewed was 6 (six) people including 1 (one) operational manager, 4 (four) division heads from each department and 1 (one) employee from the marketing department. The data analysis method includes 3 (three) activities, namely data reduction, data display and drawing conclusions. The results of the study indicate that employee work discipline is still lacking, several things that must be considered are the employee's discipline attitude to the company and the sanctions given by the company to its employees as well as compensation for incentive payments must be in accordance with the promised date.